A Study of Biomass Concrete Reinforced with Fiber Composites to Enhance Impact Load Capacity - Sakkampang, Kunanon; Tasenhog, Piyorus; Onsalung, Nirut; Huchaiyaphum, Narong (Salehan Institute of Higher Education, 2025)
This research investigates the energy absorption from impact forces of steel reinforced concrete using fly ash obtained from agricultural processes, reinforced with glass fiber-reinforced polymer (GFRP) bars, compared to steel reinforcement. The reinforcement pattern involves incorporating GFRP bars into a square grid pattern of 4, 9, and 12 openings within bio-steel concrete with dimensions (W × L × H) of 40 × 40 × 10 cm. The testing is conducted using a Drop Test impact testing machine with a 30 kg hammer head at a velocity of 7 m/s, employing two different hammer head configurations: flat and 45-degree angled, to study energy absorption (Ea), specific energy absorption (Es), and the pattern of deformation resulting from impacts. The study finds that CBRHA-10-fiber A concrete exhibits higher energy absorption and specific energy absorption compared to steel-reinforced (CBRHA-10-steel A) concrete in the same configuration by 18.82% and 26.83%, respectively, in the flat-headed hammer impact configuration. Similarly, in the 45-degree angled hammer head configuration, CBRHA-10-fiber A concrete demonstrates superior energy absorption and specific energy absorption compared to steel reinforcement in the same configuration by 6.10% and 14.92%, respectively. In conclusion, bio-steel reinforced concrete with glass fiber-reinforced polymer (GRFP) reinforcement exhibits good load-bearing capacity and suitability as an alternative to steel reinforcement in future applications. Doi: 10.28991/CEJ-2025-011-02-020 Full Text: PDF